PENGGUNAAN METODE GANJARAN DALAM MENINGKATKAN MOTIVASI BELAJAR BAHASA ARAB SISWA DI MAS BAHRUL HIKMAH KONAWE UTARA SULTRA - Gani, Yusnindar Abd (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
This study aims to describe descriptively about the use of learning methods in improving the motivation to learn Arabic students at Mas Bahrul Hikmah Konawe Utara Sultra to find out what methods are applied during the learning process at Mas Bahrul Hikmah Konawe Utara and to find out how students learn motivation of Mas Bahrul Wisdom of North Konawe. The method used in this study is a descriptive qualitative method to provide an explanation of the use of learning methods in improving the motivation to learn Arabic students at Mas Bahrul Hikmah Konawe Utara Sultra. Data obtained through interviews with research informants related to the achievement of research objectives. Subjects in this study were teachers and students at Mas Bahrul Hikmah Konawe Utara Sultra. The results of the study can be concluded: 1) The method applied when learning Arabic in Mas Bahrul Hikmah is, the method of conversation or muhadatsah, the method of reading is qira'ah (muthala'ah), grammatical or qowa'id (al-kitabah) and listening method (al-istima'i) this method is commonly used when imla learning process, besides using a special method of learning Arabic also uses common methods, such as lecture method, discussion method, group work method, question-answer method and method assignment. There is also the addition of a new method, namely, the reward method. The reward method applied is the method of giving punishment and the method of giving gifts. 2) The use of reward methods in Mas Bahrul Hikmah is very effective in addition to growing students 'motivation in learning as well as helping students obtain high test scores, because after the use of reward methods the students' test scores increase a lot.